How we write now living with Black feminist theory - Nash, Jennifer Christine 1980- (Duke University Press, 2024)
"Jennifer C. Nash's How We Write Now offers a conceptual framework for thinking about contemporary Black feminist writing's commitment to sitting with and at the scene of loss through beautiful writing. Nash argues that Black feminism is characterized by this beautiful voice-an intimate invitation to its reader, a poetic language, an investment in the aliveness of words. Further, this voice allows Black feminists to treat loss as an aesthetic question, how to sit intimately with the regularity and massiveness of the loss that is paradigmatic of Black life. In identifying this voice now, Nash also points to a proliferation in Black feminist texts of writing about mothers and motherhood, as well as the loss that binds them together. Written out of living with the loss of Nash's own mother to progressive Alzheimer's, How We Write Now performs the forms of Black feminist writing it describes and canonizes, allowing its reader to live alongside slow loss with urgency and intimacy"--
Bevorzugte Informationsquelle Landingpage (Duke), da weder Titelblatt noch Impressum vorhanden
Keywords: Nash, Jennifer C. / 1980- / Family; African American feminists; African American women authors; African American authors; African American mothers in literature; Feminist literature / United States; Feminist literary criticism / United States; Feminist theory / United States; Féministes noires américaines; Écrivaines noires américaines; Écrivains noirs américains; Féminisme / Documentation / États-Unis; Critique féministe / États-Unis; Théorie féministe / États-Unis; Electronic books